Propuesta crossmedia de identidad cultural: mitos y leyendas orenses. - Chanatasig Bravo, Maria Del Cisne; Encalada Naula, Kevin Alejandro (Machala, 2021)
Cultural identity is a concept that has evolved over time and encompasses multiple cultural manifestations that identify a place, community, country or nation. The many cultural manifestations that are part of a cultural identity are: customs, traditions, myths, legends, tales, rituals, festive events, gastronomy, clothing, parks, squares, churches, temples, monuments, streets and museums, elements that are part of a single community, creating a sense of belonging and historical social construction in human beings. The main problem shown in this research is the lack of cultural identity among Machaleños citizens, with the passage of time people have adapted foreign cultures as their own, however, this behaviour of people has affected the cultural identity of a community, devaluing the identity of a place. However, the culture of the province of El Oro is rich and immense because of its different cantons and each one with its own cultural identity, for this reason it has been chosen to work with the myths and legends of the Orenses, to highlight one of the many legends that are being lost and forgotten, because the myths and legends are part of the elements of cultural identity of intangible heritage, Work has been done on the development of a Crossmedia proposal to strengthen the cultural identity of Machaleños in the province of El Oro, which is based on communication products published by different media and social platforms. This work was carried out using a qualitative methodology in which we collected the necessary information through the research methods. The scope of the research is descriptive because it seeks to narrate stories with valuable meanings that influence the cultural identity of the audience, analyzing the studies of students from the 8th grade of basic education in the city of Machala. Through applied surveys, it was determined which communication products are to be worked on and which social platforms are frequently used. In addition, interviews were conducted with experts on the subject of cultural and narrative identity Crossmedia, taking into account the important aspects for the development of communication products and for them to have an effect on the Machalean citizenry of the province of El O. The communication products of the crossmedia proposal were disseminated through digital media and platforms, which allowed us to strengthen the myths and legends of the province of El Oro, telling the story in a creative, dynamic and appealing way for the public. On the other hand, the level of acceptance and reach of the products in the audience was calculated. The study revealed that a cross-media proposal of cultural identity made up of products such as animated videos, comics and 360o photography is a feasible idea for strengthening cultural identity in the public, as well as a viable proposal with new ideas of recreation to be used in the educational field.
La identidad cultural es un concepto que ha evolucionado con el pasar del tiempo y comprende múltiples manifestaciones culturales que identifican a un lugar, comunidad, país o nación. Las múltiples manifestaciones culturales que forman parte de una identidad cultural son; costumbres, tradiciones, mitos, leyendas, cuentos, rituales, actos festivos, gastronomía, vestimenta, parques, plazas, iglesias, templos, monumentos, calles y museos, elementos que forman parte de una sola comunidad, creando un sentido de pertenencia y construcción social histórica en los seres humanos. La problemática principal que se muestra en esta investigación, es la falta de identidad cultural, en los ciudadanos machaleños, con el pasar del tiempo las personas han ido adaptando culturas extranjeras como propias de ellos, no obstante, este actuar de las personas ha afectado la identidad cultural propia de una comunidad, desvalorizando la identidad de un lugar. Sin embargo, la cultura de la provincia de el Oro, es rica e inmensa por sus diferentes cantones y cada uno con una identidad cultural propia, para ello se ha elegido trabajar con los mitos y leyendas orenses, para destacar una de tantas leyendas que se están perdiendo y quedando en el olvido, debido a que los mitos y las leyendas forman parte de los elementos de identidad cultural de patrimonio inmaterial, se ha trabajado en la elaboración de una propuesta Crossmedia para fortalecer la identidad cultural en los ciudadanos machaleños de la provincia de El Oro, la cual está basada en productos comunicacionales que se publican por diferentes medios y plataformas sociales. Este trabajo se llevó a cabo mediante una metodología de carácter cualitativo donde recolectamos la información necesaria a través de los métodos de investigación, el alcance de la investigación es descriptivo porque busca narrar historias con significados valiosos que influyen en la identidad cultural de la audiencia, teniendo como análisis de estudios a estudiantes de 8vo de educación básica de la ciudad de Machala. Mediante encuestas aplicadas, se determinó cuáles son los productos comunicacionales en los que se va a trabajar y cuáles son las plataformas sociales que utilizan con frecuencia, además se realizaron entrevistas a expertos en el tema de identidad cultural y narrativa Crossmedia, teniendo en cuenta los aspectos importantes para la elaboración de los productos comunicacionales y que estos lleguen a causar efecto en la ciudadanía machaleña de la provincia de El Oro. Los productos comunicacionales de la propuesta crossmedia fueron difundidos mediante medios y plataformas digitales, los cuales nos permitió fortalecer los mitos y las leyendas de la provincia de El Oro, narrando la historia de una manera creativa, dinámica y atractiva para el público, por otra parte, se calculó el nivel de aceptación y alcance que tuvieron los productos en la audiencia. El estudio de la investigación permitió conocer que una propuesta crossmedia de identidad cultural conformada por productos como; videos animados, cómic y fotografía 360º es una idea factible para el fortalecimiento de identidad cultural en el público, además es una propuesta viable con nuevas ideas de recreación para ser utilizada en el ámbito educativo.
Keywords: IDENTIDAD CULTURAL; PATRIMONIO CULTURAL; PROPUESTA CROSSMEDIA; LENGUAJE AUDIOVISUAL